On the relationships between the biological realm and the semiotic realm - Gil, Jose Maria (2014)
It could be suggested that every semiotic interpretation is represented in the cognitive systems of an individual. Since they are located in the brain, the cognitive systems have to be biological. However, in some complementary way, the structure and the function of such biological systems are conditioned by semiotic information, and semiotic information has its origin in the cultural environement of the individual. In other words, depending on the point of view, every semiotic interpretation can be considered not only in terms of the social context, but also in terms of the natural world. I aim at showing that Neurocognitive Linguistics (Lamb 1999, 2004, 2005, 2006) helps us to understand that there is a biological basis for the semiotic realm. Concretely, relational networks developed by this neurolinguistic theory (which are neurologically plausible) help us to represent (some part of) the linguistic and cognitive systems of an individual. Those systems, which must have their biological basis in the brain, allow an individual to produce or to interpret signs, which are not part of such internal systems.